MULTIPLIER EFFECT OF SEA TURTLE CONSERVATION WORKING TOWARD APAR VILLAGERS NORTH PARIAMAN REGENCY PARIAMAN CITY WEST SUMATERA PROVINCE - Maharani, Veny; Hamid, Hamdi; Bathara, Lamun (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted on Desember 2015 until January 2016 at UPT Sea Turtle Conservation of Pariaman and Apar Village, North Pariaman Regency, Pariaman City, West Sumatera Province. The purpose of this research were 1) to know the conditon of the UPT Sea Turtle Conservation of Pariaman and characteristic of the visitors, trader, and local people 2) to know and analyze multiplier effect of UPT Sea Turtle Conservation of Pariaman’s activity toward the local people economic 3) to know how was the controling of conservation by stakeholder toke part its development. The method used in for this research was survey method, with 57 respondents. There are visitors, trader, local people and head of UPT Sea Turtle Conservation of Pariaman.Based on the result of the research, Sea Turtle Conservation of Pariaman has some activities such as break up of the sea turtle’s eggs, take care of sea turtle, take it to the sea, handly craft and sales food and drinks. According the formula, The Sea Turtle Conservation of Pariaman giving multiplier effect as 1.34. the controling has done based on stakeholder area. Such as promotions, give a train or knowledge and also take care of UPT Sea Turtle of PariamanKeyword : Sea Turtle Conservation, Multiplier Effect, Apar Village